Comparison of selective media for isolation of Campylobacter jejuni/coli. Issue 1 (January 1983) - Bolton, FJ; Coates, D; Hinchliffe, PM; Robertson, L
Abstract : A comparison of Skirrow's, Butzler's, Blaser's, Campy-BAP and Preston media for Campylobacter spp was made using human, animal and environmental specimens. Butzler's medium gave the lowest isolation rate and Preston medium, which was the most selective, the highest isolation rate. Enrichment culture using Preston enrichment broth gave a higher isolation rate than direct plating onto Preston medium.